Bellwether of the Canaries: anthropogenic effects on the land snail fauna of the Canary Islands - Wall, Alexander F.; Yanes, Yurena; Miller, Joshua H.; Miller, Arnold I. (Biodiversity and conservation, 2018)
Natural areas near human-modified landscapes experience factors that may affect local biodiversity at levels commensurate with natural environmental factors. The land snails of the Canary Islands provide excellent opportunities to evaluate the importance of anthropogenic agents in mediating the diversity and distribution of species. Land snails are particularly sensitive to disturbance and are an integral part of terrestrial ecosystems. This study analyzed the distributions and abundances of terrestrial macrosnail shell assemblages at 60 localities throughout the coastal scrub biome of the Canary Islands. This was accomplished using data on natural and anthropogenic variables to assess their relative importance in governing land snail diversity. A total of 34,801 dead shells represented a diverse malacofauna with highly localized endemism. Due to uncertain species identifications, samples from the 18 sites from the two easternmost islands are described, but excluded from statistical analyses. Regression tree analysis indicated that proximity to agricultural sites was the most important predictor of species diversity. Sites with no or very little agricultural area (≤ 0.167 km 2 ) within a 1 km radius had significantly higher richness and diversity. These results have implications for Canary Islands conservation. Protected areas that are patchworks of natural and agricultural landscapes are still subject to native biodiversity loss because of anthropogenic impacts even when the footprint of agriculture is small.